Penerapan Pendekatan Keterampilan Proses Untuk Meningkatkan Kemampuan Mahasiswa PGSD UPP Bone Pada Mata Kuliah Konsep Dasar IPA II - Muhammad Amran; Adnan K (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to improve the ability of PGSD UPP Bone students in the basic science basic 2 course using process skill approach. The benefits of the research are: (1) Expected Lecturer has knowledge of the theory of process skill approach which is one of the forms of learning innovation in elementary school. (2) it is expected that the lecturer in the course has a learning theory that can be used as a reference to improve the science learning outcomes. The population of the study was UPP PGSD Bone class 25.C was 19 students. Technique of collecting data of this research is by test, direct interview, observation and field note. Data analysis using descriptive statistical techniques to describe student learning outcomes. The results of the study are as follows; (2) Lecturer still have to maximize in designing lesson plan by using process skill approach, (3) Lecturer must improve competence in using a process skill approach. The improvement of students ability by using approach of process skill because student at the time learn more active in implementation of learning process.